Strategi komunikasi pemasaran 5.0 untuk meningkatkan brand awareness pada bisnis properti: Studi kasus The Sanctuary Collection - Ayu Ria Lestari; Tria Patrianti (LP2M Universitas Sarjanawiyata Tamansiswa, 2025)
Marketing communication strategies play a crucial role in the property business sector. The development of communication technology has led to a new innovation known as Marketing 5.0. This study differs from Des Derivanti et al. (2023), who focused on social media, while Timbang (2023) recommended the use of virtual reality and online media as part of a responsive promotional approach to consumers. The aim of this research is to analyze the application of Marketing Communication 5.0 in building brand awareness for The Sanctuary Collection. The study uses a qualitative case study approach with data collection techniques including in-depth interviews with three internal informants (Head of Sales & Marketing Communication, Promotion Supervisor, and Sales Manager), as well as three external informants from the consumer side, supported by observation and documentation. The validity of the data was tested through source and method triangulation and validated by experts in Public Relations and Marketing Communication. The analysis used is qualitative descriptive to identify the patterns of communication strategies applied. The research findings show that the strategy is carried out in three stages. The planning stage includes audience identification, communication objectives, message design, channel selection, and budgeting. The implementation stage involves the use of Data-Driven Marketing, Predictive Marketing, Contextual Marketing, and Augmented Marketing through 360-degree virtual tours and AI-based CRM (Mekari Qontak). Agile Marketing strategies are used to respond to market dynamics. The evaluation stage is conducted routinely using both digital and offline KPI indicators and consumer feedback.